2014
DOI: 10.1155/2014/912821
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NAMPT in Human Gingival Fibroblasts and Biopsies

Abstract: Adipokines, such as nicotinamide phosphoribosyltransferase (NAMPT), are molecules, which are produced in adipose tissue. Recent studies suggest that NAMPT might also be produced in the tooth-supporting tissues, that is, periodontium, which also includes the gingiva. The aim of this study was to examine if and under what conditions NAMPT is produced in gingival fibroblasts and biopsies from healthy and inflamed gingiva. Gingival fibroblasts produced constitutively NAMPT, and this synthesis was significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 43 publications
8
55
0
1
Order By: Relevance
“…Moreover, periodontopathogens, such as P. gingivalis , were capable of inhibiting the adiponectin expression and stimulating the expression of its receptors. These novel observations are in accordance with our previous study, which has demonstrated a downregulation of adiponectin and an upregulation of its receptors in gingival biopsies from periodontally diseased subjects as compared to periodontally healthy individuals [48]. Our findings also concur with the clinical observations that plasma adiponectin levels are decreased in periodontitis and increased again after periodontal therapy [47, 7375].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, periodontopathogens, such as P. gingivalis , were capable of inhibiting the adiponectin expression and stimulating the expression of its receptors. These novel observations are in accordance with our previous study, which has demonstrated a downregulation of adiponectin and an upregulation of its receptors in gingival biopsies from periodontally diseased subjects as compared to periodontally healthy individuals [48]. Our findings also concur with the clinical observations that plasma adiponectin levels are decreased in periodontitis and increased again after periodontal therapy [47, 7375].…”
Section: Discussionsupporting
confidence: 93%
“…As in our previous studies, cells were exposed to IL-1 β , which was used to mimic inflammatory conditions in vitro [43, 46, 48, 50]. This proinflammatory cytokine is increased in GCF and gingival tissues at inflamed sites [7678].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an in vitro study 40 demonstrated that periodontopathogenic bacteria and inflammatory stimuli caused a significant downregulation of leptin and its receptor in periodontal ligament cells, which might explain, at least in part, the reduced GCF leptin levels found in periodontally diseased sites by other clinical studies. Furthermore, enhanced expression and protein levels of visfatin were found in gingival biopsies from sites of periodontitis compared with periodontally healthy gingiva, and this production was increased under infectious and inflammatory conditions 41 . According to those authors, the local production of visfatin by periodontal ligament cells and gingival fibroblasts may contribute to the enhanced gingival levels of visfatin observed in patients with periodontitis and may represent a possible pathomechanism whereby periodontal infections may have an impact on systemic diseases such as T2DM.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, it was found that saliva visfatin levels were higher in patients with periodontitis than in the healthy individuals, which decreased at 3 months and remained low until 6 months. In several studies, high levels of visfatin have been reported in saliva, GCF, and periodontal tissue in periodontitis 6,7,41‐43 . In contrast, visfatin GCF and saliva levels have been reported to decrease after NSPT 15–18 .…”
Section: Discussionmentioning
confidence: 99%